Navigating strategic decisions : the power of sound analysis and forecasting - Triantis, John E., 1944- (CRC Press, Taylor & Francis Group, 2013)
Based on four decades of experience and research, Navigating Strategic Decisions: The Power of Sound Analysis and Forecasting explains how to improve the decision-making process in your organization through the use of better long-term forecasts and decision support. Filled with time-tested methodologies and models, it provides you with the tools to establish the organization, processes, methods, and techniques required for analyzing and forecasting strategic decisions. Describing how to foster the conditions required for forecasts to materialize, this book will help you rank project valuations.